Santa Rosa de Lima: valores y virtudes fundamentales en una formación de calidad - Aguilar Berrospi, Milner (2010)
Santa Rosa de Lima appears asan ideal el ose toman and woman of the XXI century considering the heart of every human is the same for all at all times, a heart that continues to desire love, happiness, plenitude, beauty and in essence this means to reach sanctity. For that reason, the thesis of this exposition is to affirm that sanctity is a call. This life ideal, also possible in today 's society, is expressed beautifully by two virtues that are born in the inner self, and when expressed can cause a transformation: charity and prayer. Charity is understood as the constant, self-less giving of one's being for good of others, and praying is understood as the constant possibility of discovering my own originality by encountering God.